It Risk Assessment Enterprise Architecture Grand Design Riau Menggunakan Metode FMEA - Mutia Sari Zulvi (Politeknik Caltex Riau, 2022)
Information Technology (IT) has an important role for an organization in supporting business activities. The implementation of IT supports the transformation of business processes, reduces operational costs (reduce costs), improves service quality to consumers, and ultimately supports organizational performance improvement. In line with the development of IT, currently IT is seen not only as a tool for business activities, more than that, IT has a strategic role in achieving the organization's business goals. In order to achieve this goal, it is necessary to support adequate IT management so that the existence of an IT infrastructure is needed. Of course, all forms of IT utilization and processing cannot be separated from threats to data integrity and network security. The Riau Provincial Government as part of the Unitary State of the Republic of Indonesia which is aware of the demands of the develop 1ent of ICT already has many Information Systems, especially in Diskominfo. In achieving the organization's business goals requires risk management for success or smooth achievement. According to Emmett Vaughan and Therese Vaughan, risk management is a scientific approach that aims to overcome all risks by anticipating losses that occur and implementing procedures that are able to minimize losses. There are various methods and tools for risk management analysis, one of which is quite popularly used is FMEA (Failure Mode & Effect Analysis). The results of the analysis show that the greatest potential for failure is hardware damage due to irregular maintenance and improper use of RPN 144. Based on the analysis carried out, it can be seen what potential failures have the highest RPN value that must be prioritized first.